Estudio de prefactibilidad para la instalación de una planta procesadora de conservas de arándanos en almíbar - Cabezas Uribe, Sophia Cristina (2020)
The objective of this study is to determine the pre-feasibility of the installation of a processing plant for canned blueberries in syrup in containers of musa balbisiana by evaluating the market, technological, economic and financial viability.